Identity theft: MyKad / Sheza Lina Mohd Salleh-Hud-Din, Yasmin Natasha Muhammad Khairy Nunis and Azianiziani Abdullah - Mohd Salleh-Hud-Din, Sheza Lina; Muhammad Khairy Nunis, Yasmin Natasha; Abdullah, Aziani Ziani (2008)
This project paper is written by means of a purpose to discuss the crime of identity theft that specifically focuses on MyKad. Identity theft can be described as a crime in which someone wrongfully obtains and uses another person personal data in unlawful manner, which involves fraud or deception, typically to gain profit out of it. Regularly, the identity thieves use the victims' personal information to open a bank account under the victims' name and write bad checks on that account, and in some cases, the criminals file for bankruptcy under the victims' names to avoid paying debts they have incurred under the victim's name, or to avoid eviction. As a result, the victim would suffer economic loss and his or her reputation would be affected. The main purpose of conducting this research is to inform and educate the public at large as to the nature and effects of the crime of identity theft in depth. The public need to have knowledge on this issue in order to prevent the growth of this crime. Secondly is to identify as to how the law governs the crime and the effectiveness of the present law. Currently, the law applicable varies according to the circumstances of the case. There is no standard law that governs the crime throughout the nation. The next purpose is to identify the weaknesses of the security system of MyKad. There is a need to overcome the weaknesses of MyKad in providing an effective security system of the smart card in order to cope with the crime. Next, the research aims to seek any protections for the victims of identity theft as well as to other cards holders. This is necessary, as the crime is a silent crime and it causes harm to one's life, future and reputation.